Assessment of X-band earth-satellite link rain attenuation prediction in Malaysia - Badron, Khairayu; Ismail, Ahmad Fadzil; Hasan, Mohamad Kamrul; Ismail, Mazslan; Ooi, Sock Teng; Daim, Terence Jerome (INSI Publications, 2014)
Predicted rain fade values for an Earth-satellite link operating at X-band frequency had been generated using the latest ITU-R Recommendation, P618-11. Rain fade values for the very same link were also estimated using the "radar-derived attenuation" technique. The radar technique involves the exploitation of vertical polarization S-band meteorological radar reflectivity information to calculate the possible rain attenuation along the satellite propagation paths. All estimated rain fade values were then compared with the actual measured signal of RazakSAT’s X-band satellite transmission. The measured X-band (8 GHz) transmission signals were collected and analyzed at the Malaysian National Space Agency (NSA) space center. Objective: Preliminary findings concerning the feasibility of each estimation technique are presented in this paper. The research also attempts to investigate the validity of the mentioned rain attenuation estimation techniques. Results: Preliminary findings concerning the feasibility of each estimation technique are presented in this paper. The research also attempts to investigate the validity of the mentioned rain attenuation estimation techniques. Conclusion: Such knowledge can be considered critical for the design of reliable Earth-Space communication link and certainly can be used in the preliminary proposition plan for the link designers as well as engineers.